Performance of STATCOM-ES in Mitigating SSR - Mala R.C; Nagesh Prabhu; Gururaja Rao H.V (Institute of Advanced Engineering and Science, 2017)
One of the advanced power applications using energy storage is the integration of energy storage technologies with VSC-based FACTS controllers. With the support of energy storage device, FACTS controllers will have the ability to exchange active power or energy with the ac network in steady state. This paper discusses the impact of Static Synchronous Compensator incorporating energy storage device (STATCOM-ES) on subsynchronous resonance (SSR). It also proposes the design of an auxiliary SSR damping controller (SSDC) for STATCOM-ES to damp the subsynchronous oscillations which the system is undergoing because of a series capacitor in the transmission system. The system under consideration is IEEE FBM which is modified to incorporate STATCOM-ES at the electrical midpoint. The investigation of SSR characteristics when a STATCOM - ES operating in bus voltage regulation mode is carried out by eigenvalue and damping torque analysis. Transient analysis based on the nonlinear model is also performed to validate the results obtained by conventional methods.